1995
DOI: 10.1029/94jb02642
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a high‐velocity slab associated with the Hindu Kush seismic zone

Abstract: We used teleseismic travel time residuals to determine lateral velocity variations of the crust and upper mantle in the Pamir‐Hindu Kush region in Tadjikistan and Afghanistan. Data from 29 analog seismic stations in Tadjikistan and northern Afghanistan were used to determine travel time residuals for 210 teleseismic events ranging in distance from 28° to 87° and covering a broad range of azimuths. We inverted for velocity perturbations over a rectangular grid with a block size of 99 × 99 km. The model extended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…The stronger and thinner oceanic crust results in denser and thinner W-B zone below 200 km in the east end of the Hindu Kush zone. High velocity at depth greater than 200 km and low velocity above 200 km revealed by some tomographic images (Vinnik et al, 1977;Roecker, 1982;Hamburger, et al, 1992;Mellors et al, 1995) are consistent with the idea of transition from a continental slab to an oceanic slab. However, tomographic features showed by different authors are different and need further confirmation (Koulakov and Sobolev, 2006;Huang and Zhao, 2006) Secondly, the Harvard CMT solutions in the double-layered W-B zone in Hindu Kush does not exhibit systematic differences between the two layers (Lou et al, 2007), which further validates that the earthquake hypocenters of the double-layered W-B zone in Hindu Kush region delineate two subducting slabs.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…The stronger and thinner oceanic crust results in denser and thinner W-B zone below 200 km in the east end of the Hindu Kush zone. High velocity at depth greater than 200 km and low velocity above 200 km revealed by some tomographic images (Vinnik et al, 1977;Roecker, 1982;Hamburger, et al, 1992;Mellors et al, 1995) are consistent with the idea of transition from a continental slab to an oceanic slab. However, tomographic features showed by different authors are different and need further confirmation (Koulakov and Sobolev, 2006;Huang and Zhao, 2006) Secondly, the Harvard CMT solutions in the double-layered W-B zone in Hindu Kush does not exhibit systematic differences between the two layers (Lou et al, 2007), which further validates that the earthquake hypocenters of the double-layered W-B zone in Hindu Kush region delineate two subducting slabs.…”
Section: Resultssupporting
confidence: 86%
“…However, in the deeper part the slab seems not having this kind of difference, at least not significant. Therefore, it is more likely that the shallower and the deeper parts of the W-B zone locate in decoupled continental and the oceanic plates respectively, which was revealed earlier by geophysical inversion (Roecker, 1982;Mellors et al, 1995).…”
Section: Data Processing and The Applicability Of The Hypodd Programmentioning
confidence: 88%
See 2 more Smart Citations
“…This surface-wave CMT methodology, which yields compatible and very similar results as in standard CMT, allows study of the complex processes of stress transfer to different fault segments that marked the unusual time evolution of the sequence (Arvidsson and Ekström 1998;Ekström et al 1998;Morelli et al 2000). Several workers (Menke and Jacob 1976;Armbruster et al 1978;Chatelain et al 1980;Seeber et al 1981;Ni and Ibenbrahim 1991;Fan et al 1994;Mellors et al 1995;Lukk et al 1995;Zhu et al 1997;Searle et al 2001;Khan 2003) have studied the seismicity and the geological processes of the northwestern part of the Indian plate, and have suggested that the seismicity in this region is apparently caused by the mutual interaction between the Kohistan Arc and the Indian plate (Fig. 1).…”
Section: Study Of Seismicitymentioning
confidence: 79%